REVIEW: A STUDY ON THE USE OF GOTU KOLA EXTRACT (Centella asiatica (L.) Urb.) AS A TREATMENT FOR ACNE - Endang Diyah Ikasari; Tris Harni Pebriani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Acne is an inflammatory skin condition caused by sebaceous follicles and characterized by skin inflammation in the form of a buildup of bacteria and oil that clogs pores and causes acne. Centella asiatica (L.) Urb., often known as gotu kola, has antibacterial properties that inhibit Propionibacterium acnes, thereby reducing papules, pustules, and nodules. Antioxidants, asiatic acid, and madecassic acid found in gotu kola (Centella asiatica (L.) Urb.) can treat wounds. Skin damaged by acne can be repaired and rejuvenated with gotu kola antioxidants, which also help collagen formation more quickly in the skin. This research aims to examine the ability of gotu kola (Centella asiatica (L.) Urb.) extract to inhibit acne-causing bacteria (Propionibacterium acnes) resulting from a literature review. This research method is a literature review or literature review. Research journals that met the inclusion criteria (activity test results suppressing bacterial growth activity) were collected, and a journal summary was made. A summary of the research journals is included in the table sorted by the year of publication of the journal. Based on the results of a literature review carried out by researchers, Gotu kola can be extracted using the maceration method by soaking the plant material in an extraction solvent such as ethanol or water for a specified time. This process was used to remove the active components from the plant material. The inhibition zone formed was evaluated to determine the effectiveness of the extracts or preparations containing gotu kola extract in preventing bacterial growth ...